Chronic Administration of COVID-19 Drugs Fluvoxamine and Lopinavir Shortens Action Potential Duration by Inhibiting the Human Ether‐à‐go‐go–Related Gene and Cav1.2 - Zheng, Zequn; Cai, Dihui; Fu, Yin; Wang, Ying; Song, Yongfei; Lian, Jiangfang (Frontiers in Pharmacology, 2022)
Background: Old drugs for new indications in the novel coronavirus disease of 2019 (COVID-19) pandemic have raised concerns regarding cardiotoxicity, especially the development of drug-induced QT prolongation. The acute blocking of the cardiac hERG potassium channel is conventionally thought to be the primary mechanism of QT prolongation induced by COVID-19 drugs fluvoxamine (FLV) and lopinavir (LPV). The chronic impact of these medications on the hERG expression has yet to be determined. Methods: To investigate the effect of long-term incubation of FLV and LPV on the hERG channel, we used electrophysiological assays and molecular experiments, such as Western blot, RT-qPCR, and immunofluorescence, in HEK-293 cells stably expressing hERG and human-induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs). Results: Compared to the acute effects, chronic incubation for FLV and LPV generated much lower half-maximal inhibitory concentration (IC50) values, along with a left-shifted activation curve and retarded channel activation. Inconsistent with the reduction in current, we unexpectedly found that the chronic effects of drugs promoted the maturation of hERG proteins, accompanied by the high expression of Hsp70 and low expression of Hsp90. Targeting Hsp70 using siRNA was able to reverse the effects of these drugs on hERG proteins. In addition, FLV and LPV resulted in a significant reduction of APD90 and triggered the early after-depolarizations (EADs), as well as inhibited the protein level of the L-type voltage–operated calcium channel (L-VOCC) in hiPSC-CMs. Conclusion: Chronic incubation with FLV and LPV produced more severe channel-blocking effects and contributed to altered channel gating and shortened action potential duration by inhibiting hERG and Cav1.2.